Patterns of fatigue and association with disease activity and clinical manifestations in systemic lupus erythematosus - Arnaud, Laurent; Mertz, Philippe; Amoura, Zahir; Voll, Reinhard E.; Schwarting, Andreas; Maurier, Francois; Blaison, Gilles; Bonnotte, Bernard; Poindron, Vincent; Fiehn, Christoph; Lorenz, Hanns-Martin; Korganow, Anne-Sophie; et al. (Rheumatology, 2021)
Objective. The prevalence of fatigue is high in patients with systemic lupus erythematosus (SLE). In this study, we used latent class analysis to reveal patterns of fatigue, anxiety, depression and organ involvement in a large international cohort of SLE patients. Methods. We used the Lupus BioBank of the upper Rhein to analyse patterns of fatigue using latent class analysis (LCA). After determining the optimal number of latent classes, patients were assigned according to model generated probabilities, and characteristics of classes were compared. Results. A total of 502 patients were included. Significant fatigue, anxiety and depression were reported by 341 (67.9%), 159 (31.7%) and 52 (10.4%) patients, respectively. LCA revealed a first cluster (67.5% of patients) with low disease activity [median (25th-75th percentile interquartile range) Safety of Estrogens in Lupus Erythematosus National Assessment (SELENA)-SLEDAI: 2 (0-4)], significant fatigue (55.5%, P< 0.0001), low anxiety (11.8%, P< 0.0001) and depression (0.9%, P< 0.0001). Cluster 2 (25.3%) also comprised patients with low disease activity [SELENA-SLEDAI: 2 (0-6)], but those patients had a very high prevalence of fatigue (100%, P< 0.0001), anxiety (89%, P< 0.0001) and depression (38.6%, P< 0.0001). Cluster 3 (7.2%) comprised patients with high disease activity [SELENA-SLEDAI: 12 (8-17), P < 0.0001] and high fatigue (72.2%, P< 0.0001) with low levels of anxiety (16.7%, P< 0.0001) and no depression (0%, P< 0.0001). Conclusion. LCA revealed three patterns of fatigue with important practical implications. Based on these, it is crucial to distinguish patients with active disease (in whom remission will be achieved) from those with no or mild activity but high levels of fatigue, depression and anxiety, for whom psychological counselling should be prioritized.